Regulatory volume increase (RVI) and regulatory volume decrease (RVD) responses in HL-1 cardiac myocytes - Cacace, Verónica Inés (2014)
Background/Aims: we have investigated whether cultured cardiomyocytes of the cell line HL-1 have the ability to perform regulatory volume responses both in hypotonic and hypertonic conditions. Furthermore, we characterized those regulatory responses and studied the effects of bumetanide and DIDS in volume regulation of HL-1 cells. Methods: we used a light scattering system to measure the transient volume changes of HL-1 cells when subjected to osmotic challenge. Results: We found that HL-1 cells correct for their volume excess by undergoing regulatory volume decrease (RVD), and also respond to hypertonic stress with a regulatory volume increase (RVI). Rate of RVD was 0.08 ± 0.04 intensity/min, and rate of RVI was 0.09 ± 0.01 intensity/min. Volume recovery was 83.68 ± 5.73 % for RVD and 92.3 ± 2.3 % for RVI. Bumetanide 50 µM inhibited volume recovery, from 92.3 ± 2.3 % (control) to 24.6 ± 8.8 % and reduced the rate of RVI from 0.070 ± 0.020 intensity/min (control) to 0.010 ± 0.005 intensity/min. 50 µM DIDS reduced volume recovery to 42.93 ± 7.7 % and rate of RVI, to 0.03 ± 0.01 intensity/min. Conclusions: these results suggest that bumetanide- and DIDS-sensitive mechanisms are involved in the RVI of HL-1 cells, which points to the involvement of the Na cotransporter and Cl bicarbonate exchanger in RVI, respectively.